2021
DOI: 10.15252/embr.202153877
|View full text |Cite
|
Sign up to set email alerts
|

FTLD‐TDP assemblies seed neoaggregates with subtype‐specific features via a prion‐like cascade

Abstract: Morphologically distinct TDP‐43 aggregates occur in clinically different FTLD‐TDP subtypes, yet the mechanism of their emergence and contribution to clinical heterogeneity are poorly understood. Several lines of evidence suggest that pathological TDP‐43 follows a prion‐like cascade, but the molecular determinants of this process remain unknown. We use advanced microscopy techniques to compare the seeding properties of pathological FTLD‐TDP‐A and FTLD‐TDP‐C aggregates. Upon inoculation of patient‐derived aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…Furthermore, the insoluble fractions extracted from the cells into which patient-derived TDP-43 seeds had been introduced showed CTF banding patterns similar to those of the patient-derived original seeds [ 217 ]. Insoluble TDP-43 extracted from FTLD-TDP type A-C cases by Sarkospin also shows differences of cytotoxicity and seeding activity in cultured cells depending on the subtype [ 79 , 176 ]. In addition, it has been reported that insoluble TDP-43 extracted from ALS cases induces the formation of phosphorylated TDP-43 inclusions with various morphologies, as observed in the brain of ALS patients in cultured cells expressing wild-type TDP-43, and that the prion-like property of insoluble TDP-43 accumulated in cultured cells is inherited after passaging of the cells [ 269 ].…”
Section: Experimental Prion-like Amplification and Transmission Of Pa...mentioning
confidence: 99%
“…Furthermore, the insoluble fractions extracted from the cells into which patient-derived TDP-43 seeds had been introduced showed CTF banding patterns similar to those of the patient-derived original seeds [ 217 ]. Insoluble TDP-43 extracted from FTLD-TDP type A-C cases by Sarkospin also shows differences of cytotoxicity and seeding activity in cultured cells depending on the subtype [ 79 , 176 ]. In addition, it has been reported that insoluble TDP-43 extracted from ALS cases induces the formation of phosphorylated TDP-43 inclusions with various morphologies, as observed in the brain of ALS patients in cultured cells expressing wild-type TDP-43, and that the prion-like property of insoluble TDP-43 accumulated in cultured cells is inherited after passaging of the cells [ 269 ].…”
Section: Experimental Prion-like Amplification and Transmission Of Pa...mentioning
confidence: 99%
“…Production of TDP-43 RRMs for NMR studies was performed as previously described ( 16 ). Production of full-length TDP-43 was performed as previously reported ( 7 ). For more details, see Supplementary materials & methods .…”
Section: Methodsmentioning
confidence: 99%
“…Production of full-length TDP-43 was performed as previously reported (7). For more details, see Supplementary materials & methods.…”
Section: Recombinant Protein Expression and Purificationmentioning
confidence: 99%
See 2 more Smart Citations